Community and Provider Perspectives on Addressing Unmet Need for Contraception: Key Findings from a Formative Phase Research in Kenya, South Africa and Zambia (2015-2016) - Cordero, Joanna Paula (Afr J Reprod Health, 2019)
Unmet need for contraception remains a challenge especially in low and middle-income countries. Community participation or the “active involvement of affected populations in all stages of decision-making and implementation of policies, programs, and services” is a precondition for attaining the highest standard of health. Participation as a key component of rights and quality of care frameworks could increase met needs. However, it has been inadequately addressed in contraceptive programs. A qualitative, exploratory methodology that included focus group discussions and in-depth interviews with community members, healthcare providers, and other stakeholders were conducted to identify domains or key thematic areas of action through which stakeholders could be engaged. The study conducted in Kenya, South Africa, and Zambia explored knowledge and use of contraceptives, barriers and enablers to access, quality of care, and participatory practices. Thematic analysis was used, facilitated by NVivo (version 10 QSR International) with a single master codebook. Comparing the thematic areas that emerged from the county data, four domains were selected: quality of care, informed decision-making, acceptability, and accountability. These domains informed the theory of change of a participatory programme aiming to meet unmet needs. Identifying possible generalizable domains establishes measurable and comparable intermediate outcomes for participatory programs despite diverse African contexts.